(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article investigates the main themes of Uzbek and Turkish folk proverbs through a comparative analysis. Key themes such as family and kinship, social relations, friendship, labor and honesty, as well as fate and philosophical reflections are examined through examples from Uzbek and Turkish proverbs. While similarities rooted in shared Turkic origins are highlighted, distinctions arising from national and cultural characteristics are also discussed.